Structure Elucidation, Antimicrobial and Cytotoxic Activities of a Halimane Isolated from Vellozia kolbekiiAlves (Velloziaceae). Issue 12 (December 2015) - Silva, Carmelita G.; Santos Júnior, Helvécio M.; Barbosa, Jussara P.; Costa, Gisela L.; Rodrigues, Felipe A. R.; Oliveira, Denilson F.; Costa‐Lotufo, Letícia V.; Alves, Ruy J. V.; Eleutherio, Elis C. A.; Rezende, Claudia M.
Abstract: A new halimane diterpene was isolated from Vellozia kolbekii Alves (Velloziaceae) and identified as (5 R, 8 R, 9 S, 13 R )‐halim‐1, 10‐ene‐15, 16‐diol (1 ). It showed cytotoxicity against three human cancer cell lines, SF‐295 (glioblastoma), MDA‐MB‐435 (melanoma), and HCT‐8 (colon adenocarcinoma). In the mechanism of cytotoxic action, halimane1 interferes in two major phases of the cell cycle: in S phase, in which DNA synthesis occurs and where it is very sensitive to damage, and G2M phase which is the phase of preparation for mitosis and mitosis itself, showing apoptosis‐inducing properties. Antimicrobial activity towards Gram ‐positive and Gram ‐negative bacteria was studied and, against Bacillus cereus, B. subtilis, Escherichia coli, and Pseudomonas aeruginosa, a MIC value of 0.025 μM was observed for halimane1, which is more active than the positive control chloramphenicol. Abstract :